Thermally Induced Wrinkling Behaviour of Automotive Decorative Films - Malayery, Mazhary Mahdy (My University, 2010)
Decorative plastic films are becoming more and more popular in the industry, substituting paint, chrome-plating and hydrographics. Thermal formability of these films is extending the uses of these materials into newer applications within industry, but early observation have shown that certain film constructions will wrinkle upon heating. Despite growing interest and markets to use these films in thermal forming processes, there is insufficient knowledge in the field to explain or compensate for these undesirable surface wrinkles. The purpose of this study is to find out what caused the wrinkles, what the underlying behaviour was and if they could be avoided.
The experiments were performed using a pressure sensitive adhesive coated decorative film, supplied by 3M Canada, which was laminated on one of two different secondary substrates (either steel or polypropylene). Samples were heated in a specially built hot stage with vacuum drawing capability at two different heating rates up to one of two final temperatures (110°C and 150°C) and cooled down at two different rates, afterwards. A CCD camera was used to track the changes in the wrinkle pattern on the surface of sample and relates its wavelength back to the corresponding transient temperature of the hot stage, which allowed on-line monitoring of wrinkle growth. Samples were cooled and then measured for their wavelength and surface roughness (represented by peak-to-valley distance (PV) and a standard roughness value, rms) using a white-light interferometer.
Heating rate was found to be the dominant factor in controlling whether wrinkles occurred or not. Only with high heating rates did this wrinkle phenomenon occur regardless of the secondary substrate use, though the thermal conductivity of that substrate will impact this heating rate if heated from that side (which is what was being done in this work). For steel laminated samples, a chaotic zigzag wrinkles occurred using fast heating rates (around 95°C/min) which had an average equilibrium wavelength of 450 μm. Plastic laminates, just like their metal counterparts, developed wrinkles but now at high heating rates (170°C/min) which produced a pattern with an average wavelength of 550 μm. The slow heating rate (≈2°C/min) did not produce wrinkles for either substrate. Wrinkles are only the final outcome of thermally induced compression stresses which build within the film sandwich construction as the temperature rises and while slower heating didn't produce wrinkles, initial blister formation still occurred (i.e. nuclei of wrinkles) which increased the surface roughness of samples. Pre-straining a sample up to 20% elongation caused the wrinkle pattern to change from a complex biaxial pattern to longitudinal stripes, which extended the pattern always present along the edges of the sample into the centre of the test specimen.
Of all models for the wrinkling behaviour of a thin film under compressive stresses in the literature, only one single model proposed by Basu et al. seemed to predict this behaviour reasonably by taking temperature and secondary substrate effects into account. All other models failed to predict this behaviour because, firstly they did not take the effects of temperature and secondary substrate into account, secondly, they
erroneously assume the film always deformed elastically, and thirdly, they are not well suited to the thickness ratio of film to substrate for our case.
Keywords: Chemical Engineering; Chemical Engineering